Sarconesiopsis magellanica (Diptera: Calliphoridae) life-cycle, reproductive and population parameters using different diets under laboratory conditions (2013)
Sarconesiopsis magellanica is a forensically relevant necrophagous blowfly that can aid in determining the post-mortem interval (PMI) as it is the first to colonise decomposing corpses. The blowfly has been reported in several South-American countries including Colombia, in high-altitude regions ranging from 1200 to 3100m above sea level. The present study reports this blowfly's life cycle and an analysis of its reproductive and population parameters under laboratory conditions for the first time. Six successive generations of flies were produced with an average of 65.38% adults emerging with respect to the total number of puparia. The shortest life cycle from egg to adult emergence was found in individuals fed on a lyophilised liver (LL) diet, while the longest one was found in individuals fed with an egg-powdered milk (E-PM) diet; intermediate values were found when the pig liver (PL) diet was tested. The greatest adult longevity was achieved when the PL diet was used, the LL diet giving the shortest. The population parameters based on the horizontal life table were: net reproductive rate (Ro)=447.752±9.9, mean generational time (Tc)=18.18±0.38, natural population increase rate (rm)=0.145 and finite population increase rate (?)=1.398. This blowfly colony represents a valuable asset for both basic and applied studies. Members of the S. magellanica colony so established were used for analysing the life-cycle, reproductive and population parameters, and further medical and forensic application studies are currently underway. © 2013 Elsevier Ireland Ltd.